ULTRASOUND VIDEO ANALYSIS FOR UNDERSTANDING INFANT BREASTFEEDING - G. Monaci; M. Woolridge ("Paediatrician" Publishers LLC, 2012)
While it has been widely proved that breastfeeding is the healthiest feeding option for a baby and its mother, the mechanisms by which a baby removes milk from the breast are still not completely known. Partly this is due to the lack of tools to analyze images of the infant oral cavity during feeding automatically and quantitatively. In this paper we propose two methods for analyzing ultrasound videos to automatically detect relevant events such sucking and swallowing of milk and to discriminate different types of tongue action during milk removal. The proposed algorithms provide, for the firrst time, quantitative indications of the type of activities carried out during breastfeeding by the baby, promising unprecedented advancements in the field.